Praperadilan Penetapan Status Tersangka Tidak Melalui Prosedur Yang Sah dan Patut Dalam Dugaan Tindak Pidana Korupsi - Mukminah, Lily Solichul (Riviera Publishing, 2025)
Pretrial is an institution that was born due to Law No. 8 of 1981 concerning the Criminal Procedure Code (KUHAP). In Article 1 number 10 of the Criminal Code, it is stated that Pretrial is the authority of the District Court to examine and decide on the legality of the termination of the investigation or prosecution an the request for compensation or rehabilitation, all of which can be done at the request of the suspect or his family or legal representative for the sake of upholding the law and justice. The Constitutional Court has expanded the object of pretrial including the legality or not of the determination of suspects, searches and seizures. This research was conducted to examine the decision of the Court Number: 12/Pid.Pra/2024/PN Ptk regarding the determination of suspect status in the alleged corruption of Land Acquisition at the West Kalimantan Provincial Regional Development Bank BANK BANK KALBAR in 2015. As for the problem, (1) What is the basis for the judge's consideration of canceling the suspect's status? (2) What are the legal consequences of the pretrial decision? In this study, the author uses normative legal research methods with a case approach, a conceptual approach, and a legislative approach. The sources of legal materials include primary legal materials in the form of the Criminal Code, Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, and Law No. 48 of 2009, secondary legal materials in the form of books, literature and legal journals related to problems, as well as tertiary legal materials in the form of KBBI, Legal Dictionary, and subsequently qualitatively analyzed and presented in analytical descriptive form. A person who is suspected of committing a criminal act of corruption who is summoned as a witness, must be examined as a witness, and if his status is raised as a suspect, then he must go through a valid and correct procedure, namely a case title is carried out first, then summoned as a suspect, and then can be detained, except for the procedure for the case of being arrested. The determination of suspect status that is not carried out through legal and correct procedures will result in the determination of the suspect's status being invalid.